2013
DOI: 10.1021/am4025966
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in the Characterization of Plasma-Processed Three-Dimensional Polymeric Scaffolds for Biomedical Applications

Abstract: Low-temperature plasmas offer a versatile method for delivering tailored functionality to a range of materials. Despite the vast array of choices offered by plasma processing techniques, there remain a significant number of hurdles that must be overcome to allow this methodology to realize its full potential in the area of biocompatible materials. Challenges include issues associated with analytical characterization, material structure, plasma processing, and uniform composition following treatment. Specific e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 55 publications
1
26
0
Order By: Relevance
“…We believe that our cross-section WCA measurements are heavily affected by the fact that when the samples are cut, untreated, hydrophobic PCL becomes exposed, and that these surfaces dominate the interaction with the water drop, resulting in limited wetting and adsorption. [38] We thus conclude that all N 2 /H 2 O treatments, in our conditions, allow scaffolds to absorb water with respect to untreated materials. This should allow better performances as cell-culture substrates both in vitro and in vivo.…”
Section: Chemical and Morphological Characterization Of The Scaffoldssupporting
confidence: 52%
See 2 more Smart Citations
“…We believe that our cross-section WCA measurements are heavily affected by the fact that when the samples are cut, untreated, hydrophobic PCL becomes exposed, and that these surfaces dominate the interaction with the water drop, resulting in limited wetting and adsorption. [38] We thus conclude that all N 2 /H 2 O treatments, in our conditions, allow scaffolds to absorb water with respect to untreated materials. This should allow better performances as cell-culture substrates both in vitro and in vivo.…”
Section: Chemical and Morphological Characterization Of The Scaffoldssupporting
confidence: 52%
“…As our cross‐section XPS data show that the surfaces of the inner pores are efficiently modified by our treatments (Figure ), we expected good water adsorption levels also in the core of the scaffolds. We believe that our cross‐section WCA measurements are heavily affected by the fact that when the samples are cut, untreated, hydrophobic PCL becomes exposed, and that these surfaces dominate the interaction with the water drop, resulting in limited wetting and adsorption . We thus conclude that all N 2 /H 2 O treatments, in our conditions, allow scaffolds to absorb water with respect to untreated materials.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…[2][3][4][5][6][7] Moreover, among various gas phase techniques, [1,[8][9][10][11][12] over the last decade, the low pressure plasma-enhanced chemical vapor deposition (PECVD) has demonstrated to be a viable approach for surface modification of porous materials, as for instance widely reported in the case of polymer scaffolds for tissue engineering applications. [1,[11][12] Deposition inside porous scaffolds is driven by the non-line-of-sight ability of low pressure plasmas for surface modification of objects with complex 3D geometries. Specifically, diffusion of reactive depositing species into the scaffold interior is thought to control thin film deposition in low pressure PECVD processes.…”
Section: Introductionmentioning
confidence: 99%
“…[1,13] Several studies reported, in fact, that limited penetration of thin film precursors within porous 3D structures can result in gradients of both coating thickness and surface chemical composition moving from the exterior to the interior of the plasma-treated substrate. [1,[11][12] Treatment uniformity throughout the entire porous structure could be improved if the discharge could ignite inside the substrate pores and, therefore, with atmospheric pressure operation. In fact, to achieve plasma ignition, pores dimension must be consistently greater than the Debye length, and for substrates having sub-millimeter pore sizes this is unlikely to occur under low pressure plasma conditions.…”
Section: Introductionmentioning
confidence: 99%